Peliosanthes chenmingsongii (Asparagaceae), a new species from Yunnan, Southwestern China - Li, Xiao Hong; Pan, Xiang Ru; Sun, Yi Fei; Yuan, Juan Juan; Feng, Hui Zhe (Phytotaxa, 2025)
Peliosanthes chenmingsongii is described and illustrated as a new species from southwestern China. The new species is morphologically closest to P. cupuliformis, but differs in its erect, woody and hard rhizome, longer petioles and larger leaf blades, more widely expanded flowers with recurved perianth segments, non-revolute margins and a horizontally inward-growing annular appendage in the corona. Careful comparisons with other closely related species are also made.